Pengaruh Volatilitas Makroekonomi terhadap Alokasi Kredit Bank - Colin, Simanjuntak Ronald; Kacaribu, Febrio (UI Scholars Hub, 2021)
This study discusses the impact of macroeconomic volatility on bank credit allocation. The hypothesis built that macroeconomic volatility will influence banks to careful in issuing new loans. This study uses panel data with a sample of 10 banks using Baum model. This study uses the macroeconomic volatility as independent variables. This study uses a generalized method of moment regression test to examine the relationship between dependent and independent variables. The results of this study indicate negative relationship between inflation volatility and volatility in GDP growth with lending, whereas the volatility of exchange rate depreciation does not have effect on lending.